Smallholder Livestock Commercialization - Roger Merkel (Indonesian Center for Animal Research and Development, 2019)
The world’s population is expected to grow by over 30% by 2050, putting tremendous strain on agriculture to produce the estimated additional one billion tons of cereal grains and 200 million tons of meat to feed that population. Most of the population growth will occur in Africa and Asia where the majority of smallholder farms are located. Commercialization of smallholder farms can lead to increased productivity. Producer identified constraints to commercialization include infrastructure, poor knowledge of market prices, limited access to banking services and loan opportunities, and poor extension services, among others. To overcome these constraints will take actions by various sectors. Producer must become more market oriented and take advantage of current technologies to improve production. Government organizations should develop ways to build farmer capacity in market and production activities. Research institutes and universities must conduct research to drive innovation, help farmers to apply technologies, and develop means to enhance producer knowledge. Making loans and banking services available to farmers is a main role of the private sector. The private sector can also partner with producers on marketing and market access.